Analysis of the Factors Affecting the Low Exclusive Breastfeeding In Pandansari Village, Senduro District, Lumajang Regency - Dinia Kholida Kiptiyah; Farianingsih Farianingsih; Homsiatur Rohmatin (NHM PRESS, 2023)
Exclusive breastfeeding is that babies are only given breast milk without other additional foods, it is recommended for up to 6 months and breastfed as early as possible. There are many reasons why mothers did not give exclusive breastfeeding to their babies, the main causes are lack of awareness of the importance of breastfeeding, lack of self-confidence of mothers, the low of mother’s knowledge about the benefits of breastfeeding and lack of family support in breastfeeding. This study aims to analyze the factors of mother's knowledge, education, and husband's support that affect the low level of exclusive breastfeeding in Pandansari Village, Senduro District, Lumajang Regency in 2022. This study is an analytic observational study with a cross sectional approach. The sample in this study were 27 mothers who had babies aged 6-11 months who were taken by total sampling. The conclusion of this study is that there is a significant relationship between the mother's knowledge factor, the mother's education factor and the husband's support factor with the low level of exclusive breastfeeding in Pandansari Village, Senduro District, Lumajang Regency. It is hoped that the Puskesmas can improve health promotion programs, especially counseling about exclusive breastfeeding, so that the achievement of exclusive breastfeeding can increase.